2021
DOI: 10.1016/j.jbo.2021.100356
|View full text |Cite
|
Sign up to set email alerts
|

N-cadherin in osteolineage cells modulates stromal support of tumor growth

Abstract: Highlights N-cadherin in osteolineage, Osterix+ cells restrains extraskeletal tumor growth. Osterix+ cells are present in the stromal microenvironment of extraskeletal tumors. Osterix+ cells are present in normal tissues frequent sites of metastasis. N-cadherin modulates pro-tumorigenic signaling in tumor associated Osterix+ cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…In another study, anti-EGFR monoclonal antibody decreased the movement of H322 and A549 cells due to increased expression of E-cadherin after treatment with mAb. These results also suggested that E-cadherin could act as a biomarker for benign NSCLC cancers 26,27 . Overall, the study implies that E-cadherin could be a biomarker for diagnosis of Non-small Cell Lung Cancer (NSCLC) cancer and our results demonstrate the possible use of Genistein as a chemotherapeutic agent for the treatment of cancer.…”
Section: Discussionmentioning
confidence: 62%
“…In another study, anti-EGFR monoclonal antibody decreased the movement of H322 and A549 cells due to increased expression of E-cadherin after treatment with mAb. These results also suggested that E-cadherin could act as a biomarker for benign NSCLC cancers 26,27 . Overall, the study implies that E-cadherin could be a biomarker for diagnosis of Non-small Cell Lung Cancer (NSCLC) cancer and our results demonstrate the possible use of Genistein as a chemotherapeutic agent for the treatment of cancer.…”
Section: Discussionmentioning
confidence: 62%